THE EFFECT OF FRAUD DIAMOND ON FRAUDULENT FINANCIAL STATEMENTS IN FOOD AND BEVERAGE SUB-SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Ari Kharisma; Windy Atmawardani Rachman (Asosiasi Dosen Muda Indonesia, 2024)
The research aimed to analyse the effect of fraud diamond components on the occurrence of fraudulent financial statements in food and beverage subsector companies listed on the Indonesia Stock Exchange (BEI). The components of fraud diamond which include as financial stability, ineffective monitoring, change in auditors, and change in directors were independent variables that were suspected to affect the fraudulent financial statement in the company. Population in this research was all financial statements of food and beverage companies listed on the Indonesia stock exchange which have been audited and published. Samples were financial statements of food and beverage companies period 2021-2022 taken through purposive sampling as many as nineteen companies. The sampling technique in this research was purposive sampling. The data analysis used is descriptive statistics, classic assumption tests using the normality test, autocorrelation test, multicollinearity test and heteroscedasticity test, multiple linear regression analysis, and hypothesis testing using the partial test (t) and simultaneous test (f). The partial results of the research are that the variables financial stability, ineffective monitoring, change in auditor, and change in director have no effect on fraudulent financial statements. The results of the research simultaneously show that the variables financial stability, ineffective monitoring, change in auditor, and change in director have no effect on financial statement fraud.